PERANCANGAN VIDEO PROMOSI FAKULTAS ILMU KEOLAHRAGAAN UNIVERSITAS NEGERI PADANG - JULISMAN, Hendra Afriwan, S.Sn., M.Sn., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
Sports Science Faculty Padang State University a Science training institutions of higher education personnel. Sports Science Faculty is the only concentration in the field of sport science.Lack of understanding of the target audience and not optimal media in disseminating information about Sports Science Faculty a major factor in Video Promotion Sports Science Faculty Padang State University. Sports Science Faculty Padang Sate University is made in the form of a Video Promotion aimed so that people can more easily understand the information Sports Science faculty. In addition to the Video Promotion information delivery is also supported by several other media that help the major media to introduce the subject to the target audience, namely posters, stickers, T-shirts, mug, pin, taperware, x-banner , and calender.The methodology used is the approach SWOT strength (strength), weakness (weakness), opportunities (opportunities), threats (threats), why (why). By using the theory SWOT, then all aspects are summarized in the procession Sports Science Faculty can be packaged into Video promotion, so the Video Promotion Sports Science faculty Padang State University can become a media that has the information factual effective and communicative for the target audience.Keywords: Video Promotion, Sports State Faculty